2022
DOI: 10.3390/cells11142153
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of a Therapy for Chronic Traumatic Spinal Cord Injury in Rats Using Human Wharton’s Jelly Mesenchymal Stromal Cells: Proof of Concept and Regulatory Compliance

Abstract: (1) Background: the use of Mesenchymal Stromal Cells (MSC) in emerging therapies for spinal cord injury (SCI) hold the potential to improve functional recovery. However, the development of cell-based medicines is challenging and preclinical studies addressing quality, safety and efficacy must be conducted prior to clinical testing; (2) Methods: herein we present (i) the characterization of the quality attributes of MSC from the Wharton’s jelly (WJ) of the umbilical cord, (ii) safety of intrathecal infusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Thus, we confirmed that both the biomaterial and the implantation procedure represent a safe therapy for transplantation in our short-term study. Furthermore, the biomaterial did not impede the migration of the cell transplants to the lesion site, similar to previous studies in which cell therapy was transplanted by intrathecal injections in preclinical models (T.-T. Cao et al 2022;Vives et al 2022). However, long-term studies should be carried out to study the long-term safety and outcomes of this non-invasive approach.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, we confirmed that both the biomaterial and the implantation procedure represent a safe therapy for transplantation in our short-term study. Furthermore, the biomaterial did not impede the migration of the cell transplants to the lesion site, similar to previous studies in which cell therapy was transplanted by intrathecal injections in preclinical models (T.-T. Cao et al 2022;Vives et al 2022). However, long-term studies should be carried out to study the long-term safety and outcomes of this non-invasive approach.…”
Section: Discussionsupporting
confidence: 82%
“…In animal experimentation for SCI studies, the use of post-operative analgesics appears to be highly uncommon [47][48][49][50]. Further, studies that do report usage of analgesia often provide minimal details on duration of therapy [51] and frequency of administration, or report non-validated analgesic regimens [52] that could be inadequate [53,54]. Further, several systematic reviews done on animal models of SCI has also overlooked the importance of usage, reporting, and risk of potential side-effects of analgesics on research data, if any [38, 43,55].…”
Section: Plos Onementioning
confidence: 99%